"Criminalization" of Humanitarian Action Under Counterterrorism Frameworks: Key Elements and Concerns. (22nd March 2019) - Lewis, Dustin A.
Abstract : Of the diverse array of contemporary challenges around humanitarian access in armed conflict, a particular set of issues concerns the so-called "criminalization" of humanitarian action under counterterrorism frameworks. This presentation raises some key elements of that set of issues.